Inventarisasi Jenis Tumbuhan Obat dan Pemanfaatannya oleh Masyarakat di Desa Malintang Kecamatan Bukit Malintang Kabupaten Mandailing Natal Sumatera Utara - Salamat Ridoan; Ferdinand Susilo; Jamilah Nasution (Jurnal Ilmiah Biologi UMA (JIBIOMA), 2022)
Medicinal plants are plants that have been identified and are known based on human observations to have bioactive compounds that have medicinal properties. This study aims to identify and describe the types of medicinal plants and their use by the community in Malintang Village, Bukit Malintang District, Mandailing Natal Regency, North Sumatra. Based on the research results obtained from interviews with  the  community  totaling  17  people  from  370  heads  of families, it can be concluded that there are 30 types of plants from 20 families that are  useful   as   medicine  in   Malintang  Village,   Bukuit   Malintang   District, Mandailing Natal Regency, North Sumatra Province. There are 16 types of plants that are used for leaf parts, 6 types of fruit parts, 5 types of rhizome parts, 4 types of flower parts, 3 types of seeds, 2 types of tubers, 1 part of the skin and roots of each plant.